From immune dysregulation to organ dysfunction: understanding the enigma of Sepsis - Liu, Zhi; Ting, Yuan; Li, Miao; Li, Yukun; Tan, Yingzheng; Long, Yunzhu (Frontiers in Microbiology, 2024)
Sepsis is a syndrome precipitated by immune dysregulation in response to infection, and represents a pivotal factor in global mortality attributed to diseases. The recent consensus delineates sepsis as a perilous state of organ dysfunction arising from the host's maladaptive reaction to infection. It masks the complexity and breadth of the immune mechanisms involved in sepsis, which is characterized by simultaneous hyperinflammation and immunosuppression. Sepsis is highly correlated with the dysregulation of immune response, which is mainly mediated by various immune cells and their interactions. This syndrome can lead to a plethora of complications, encompassing systemic inflammatory response, metabolic disturbances, infectious shock, MODS, and DIC. Furthermore, more research studies have been conducted on sepsis in the past few years. The pathological characteristics of sepsis have been improved or treated by targeting signaling pathways like NF-B, JAK-STAT, PI3K-Akt, and p38-MAPK. Combined drug therapy is better than single drug therapy for sepsis. This article will review the latest progress in the pathogenesis and treatment of sepsis.